(untitled) (Revista Argentina de Cirugía, 2022)
Background: vascular malformations of the head and neck are a group of very unfrequent and heterogeneous conditions in an adult patient. They may be source of disturbing symptoms and even become a potential life threatening disorder. Objetive: to describe surgical management and outcome of a series of eleven adult patients with vascular malformations of the head and neck. Setting: third level universitary hospital. Design: retrospective observational. Population: eleven patients (6 females and 5 males) were operated on between January 2008 and February 2013; mean age was 39 years (range 28-62). Method: review of clinical records and pathological reports. Results: according to ISSVA classification, 6 were venous malformations, 2 arteriovenous malforma- tions, 2 macrocystic lymphatic malformations, and one capilar malformations. Locations were cheek in 5 cases, lateral neck in 2, forehead and nose in one, temporal in one, tongue and lips in one, and occipital in one. All of them were resected and required different reconstructive procedures, according to size and location. Conclusions: surgical treatment of vascular malformations of the head and neck in adult patients must be tailored for individual cases and requires an experienced team for resection and reconstruction with different techniques.